White matter integrity in brain structures supporting semantic processing is associated with value-directed remembering in older adults. (June 2019) - Hennessee, Joseph P.; Reggente, Nicco; Cohen, Michael S.; Rissman, Jesse; Castel, Alan D.; Knowlton, Barbara J.
Abstract: White matter microstructure changes substantially in aging. To better understand how the integrity of white matter structures supports the selective learning of rewarding material, 23 healthy older adults were tested on a value-directed remembering task. This task involved successive free recall word lists where items differed in importance, as denoted by value cues preceding each word. White matter structure was measured using diffusion tensor imaging (DTI). We found that greater structural integrity (as measured by lower mean diffusivity) in left inferior fronto-occipital fasciculus was associated with greater recall for high-value items, but not low-value items. Older adults with greater structural integrity in a tract involved in semantic processing are thus able to more successfully encode high-value items for subsequent recall. However, unlike prior findings in younger adults, older adults' memory for high value-items was not significantly correlated with the structural integrity of the uncinate fasciculus, nor with the strength of anatomical connectedness between the bilateral nucleus accumbens to ventral tegmental area reward pathway. These structural imaging findings add support to recent functional neuroimaging demonstrations that value-related modulation of memory in older adults depends heavily on brain circuits implicated in controlled processing of semantic knowledge. Highlights: Inferior fronto-occipital fasciculus integrity associated with selective learning in older adults. Uncinate fasciculus and reward circuit integrity supported selective learning in younger adults. These findings suggest older adults rely less on traditional reward circuits when learning valuable information. Older adults may instead rely on strategic encoding and semantic processing.